Valuation of metallurgical slags as industrial resources - Lovera Dávila, Daniel (2004)
Currently, various metallurgical processes are used to obtain and recover metals, and in each one of them inevitable residues are produced, such as the formation of slags, trying to ensure that they have the lowest possible metal content and that their final residues have a later value. for other industrial processes; topic that the present investigation develops. Slag is a phase containing useless substances from a mineral, which are present in any metallurgical process involving smelting. In general, copper slags are Si02 iron silicate oxides, although there are other elements that do not exceed 20% and are therefore not taken into account. With respect to impurities, they play a negative role in its properties such as its electrical and thermal conductivity, its color, its hardness and others; They can be classified into three groups of easy elimination (Zn, Fe, 0 and S), impurities that are partially eliminated (As, Sb, Bi and Ni), and impurities that are not eliminated (Au, Ag).